(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Artistically-aesthetical education of youth and the ways of its modernization. The article is devoted to analysis o f situation o f artistically-aesthetical education of school youth in Ukraine. The ways of modernization of artistically-aesthetical education and further improvement of professional mastery of teachers of artistic disciplines are grounded.